Practices and perceptions about breastfeeding: Consensus and dissensus in the daily care in a Family Health Unit - Marques, Emanuele Souza; Cotta, Rosângela Minardi Mitre; Franceschini, Sylvia do Carmo Castro; Botelho, Maria Izabel Vieira [UNESP]; Araújo, Raquel Maria Amaral; Junqueira, Túlio da Silva (FapUNIFESP (SciELO), 2009)
This study is based on a qualitative research, and has two objectives: to identify the importance of breastfeeding for professionals who work in the Family Health Program; and to highlight convergent and divergent themes concerning breastfeeding among health care professionals and mothers. For data collection, the semi-structured and focus group were used. The study involved 17 professionals working in basic health care units and 58 mothers of children under two years old in the city of Coimbra, Mina Gerais State. The most important outcomes were that breastfeeding was regarded as an obligation by mothers, that the speech refers to the importance of a professional trained in lactation. The discourse analysis also highlighted an imbalance between the knowledge reported by the professional and daily practice of the health service. In this sense, the importance of continuing and permanent education policies are key elements for training in breastfeeding, and are indicators of health planning actions.
Práticas e percepções acerca do aleitamento materno: Consensos e dissensos no cotidiano de cuidado numa Unidade de Saúde da Família
Keywords: Breastfeeding; Family health program; Nursing mothers